(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
Literature serves as a mirror of human experience, reflecting universal values that transcend cultural boundaries. This article explores the representation of universal human values in Uzbek and American literary works and examines how these values are recreated in translation. By analyzing selected texts from both literary traditions, the study investigates how translators preserve, adapt, or reinterpret cultural nuances, moral principles, and social norms while maintaining the integrity of the original message. The article also highlights the challenges translators face in conveying culturally specific elements and emotional resonance across languages. Findings suggest that translation not only bridges linguistic gaps but also enables cross-cultural dialogue, ensuring that universal human values remain accessible and meaningful to diverse audiences.